SECTIONING OF HIGH DIMENSIONAL BANDED MATRICES - Fedasyuk, Dmytro; Serdyuk, Pavlo; Semchyshyn, Yuriy (International Journal of Computing, 2014)
Solving high dimensional systems of linear algebraic equations is of use to many problems of mathematical physics, in particular, it is one of the main subgoals at solving systems of equations in partial derivatives. Distributed solving of high dimensional systems of linear equations allows to reduce computing time, especially in cases when these matrices can not be kept in one computer's RAM. The subject of this study is the search of optimal high dimensional matrices sectioning algorithms for distributed solving systems of linear algebraic equations.